Prospects of rhizobial inoculant technology on Bambara groundnut crop production and growth - Fwanyanga, Felicitas M.; Horn, Lydia N.; Sibanda, Timothy; Reinhold-Hurek, Barbara (Frontiers in Agronomy, 2022)
Bambara groundnut (Vigna subterranea (L.) Verdc) is the third most important food legume in Africa, after peanut and cowpea (Vigna unguiculata). It is characteristically grown in marginal soils, is drought tolerant, and also has the potential for nitrogen fixation. Despite that, year-on-year Bambara groundnut yields are on a gradual decline due to a combination of abiotic and biotic stresses such as uneven annual rainfall and climate-induced changes in soil microbial community compositions, negatively impacting on food security. Thus, application of rhizobial inoculants at planting significantly improves yields in many leguminous crops. Moreover, the use of symbiotic inoculants for improvement in nitrogen fixation and productivity of grain legumes is well established in developed countries. The above practice is, however, still under-utilised in Sub-Saharan African countries. Nitrogen (N) is the key plant nutrient that stimulates root and shoots growth, which is also the most frequently deficient nutrient for crop production. While nitrogen fertilisers can be used to supplement soil N levels, they are, however, also costly, at times inadequate, may not be timely in supply, and may have deleterious environmental consequences. Rhizobial inoculants therefore, are seen to provide a cheaper, easier and safer alternative to improve the N-fixation and productivity of grain legumes, and hence food security in smallholder farming systems. Therefore, determining the most efficient rhizobial strains for biofertiliser production for Bambara groundnut is of ultimate importance to the farming communities.